Corrosion Behavior of Carbon Steels in CCTS Environment. (4th February 2016) - Cabrini, M.; Lorenzi, S.; Pastore, T.
Abstract : The paper reports the results of an experimental work on the effect of steel microstructures on morphology and protectiveness of the corrosion scale formed in water saturated by supercritical CO2 . Two HSLA steels were tested. The microstructures were modified by means of different heat treatments. Weight loss was measured after exposure at CO2 partial pressure of 80 bar and 60°C temperature. The morphology of the scale was analyzed by means of scanning electron microscope (SEM) energy-dispersive X-ray spectroscopy (EDX). Cathodic potentiodynamic tests were carried out on precorroded specimens for evaluating the effect of preformed scales on cathodic polarization curves in CO2 saturated sulphuric acid solution at pH 3, which is the value estimated for water saturated by supercritical CO2 . The results are discussed in order to evaluate the effect of iron carbide network on scale growth and corrosion rate. Weight loss tests evidenced average corrosion rate values in the range 1–2.5 mm/y after 150-hour exposure. The presence of thick siderite scale significantly reduces the corrosion rate of carbon steel. A slight decrease of the corrosion rate was observed as the scale thickness increases and moving from martensite to microstructures containing carbides.